Pengembangan bahan ajar tajwid dengan flipbook di Madrasah Tsanawiyah - Addimasyqi, Moh. Ridham; Tamam, Abas Mansur; Alim, Akhmad (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
The purpose of this study is to analyze the need for the development of tajweed teaching materials with flipbooks in MTs, make tajweed teaching materials with flipbooks in MTs, determine the feasibility of tajweed teaching materials with flipbooks in MTs and find out the level of effectiveness of tajweed teaching materials with flipbooks in MTs. The results of this study show that the majority of 97% in MTs Utsmanil Hakim and 96% agree on the need for the development of electronic-based tajweed teaching materials. The tajweed material presented in this teaching material is the science of tajweed, makhraj and the nature of letters, tarqiq and tafkhim, the law of nun sukun and tanwin, the law of mim sukun, the law of mad thabi'i and far'i, waqaf and ibtida', gharib readings developed with the Canva and Heyzine applications. The feasibility of tajweed teaching materials with flipbooks at Madrasah Tsanawiyah is validated by material, media, and language experts. Validation from media experts obtained a score of 82% classified as